FEATURES OF EDUCATIONAL AND PEDAGOGICAL WORK WITH STUDENTS OF LOW ACADEMIC PERFORMANCE - Ravshanbek Islomov Turgunalievich (International Scientific and Current Research Conferences, 2023)
This article explores the features of educational and pedagogical work with students characterized by low academic performance in an educational environment. The article discusses various aspects related to the definition of the concept of "low academic performance" and the identification of the underlying causes. The authors analyze the influence of internal and external factors on the formation of low academic performance among students, and also highlight the psychological and socio-cultural aspects of this problem. The main attention is paid to the development and implementation of effective pedagogical strategies and techniques adapted to the needs of students with low academic performance. The article discusses innovative approaches to learning, motivational methods and measures aimed at increasing students' interest in the learning process. Practical aspects of working with this category of students are also considered, including the organization of individual support, taking into account their needs and creating a favorable educational environment.